Exploring the impact of MiR-92a-3p on FOLFOX chemoresistance biomarker genes in colon cancer cell lines - Escalante, Paula I.; Quiñones, Luis A.; Contreras, Héctor R. (Frontiers in Pharmacology, 2024)
One of the primary obstacles faced by individuals with advanced colorectal cancer (CRC) is the potential development of acquired chemoresistance as the disease advances. Studies have indicated a direct association between elevated levels of miR-92a-3p and the progression, metastasis, and chemoresistance observed in CRC. We proposed that miR-92a-3p impairs FOLFOX (fluorouracil/oxaliplatin) chemotherapy response by upregulating the expression of chemoresistance biomarker genes through the activation of β-catenin and epithelial-mesenchymal transition (EMT). These FOLFOX biomarker genes include the pyrimidine biosynthesis pathway genes dihydropyrimidine dehydrogenase (DPYD), thymidylate synthase (TYMS), methylenetetrahydrofolate reductase (MTHFR), and the genes encoding the DNA repair complexes subunits ERCC1 and ERCC2, and XRCC1. To assess this, we transfected SW480 and SW620 colon cancer cell lines with miR-92a-3p mimics and then quantified the expression of DPYD, TYMS, MTHFR, ERCC1, ERCC2, and XRCC1, the expression of EMT markers and transcription factors, and activation of β-catenin. Our results reveal that miR-92a-3p does not affect the expression of DPYD, TYMS, MTHFR, and ERCC1. Furthermore, even though miR-92a-3p affects ERCC2, XRCC1, E-cadherin, and β-catenin mRNA levels, it has no influence on their protein expression. In conclusion, we found that miR-92a-3p does not upregulate the expression of proteins of DNA-repair pathways and other genes involved in FOLFOX chemotherapy resistance.